Disease severity staging system for idiopathic pulmonary fibrosis in Japan. Issue 8 (8th August 2017) - Kondoh, Yasuhiro; Taniguchi, Hiroyuki; Kataoka, Kensuke; Furukawa, Taiki; Ando, Masahiko; Murotani, Kenta; Mishima, Michiaki; Inoue, Yoshikazu; Ogura, Takashi; Bando, Masashi; Hagiwara, Koichi; Suda, Takafumi; et al.
ABSTRACT: Background and objective: In Japan, the classification of disease severity of idiopathic pulmonary fibrosis (IPF) (J‐system) has been used in making decisions on medical care subsidies. The present J‐system consists of arterial partial pressure of oxygen (PaO2 ) and exercise desaturation in stages of I–IV. It provides a good prognostic classification in stages III and IV, but not in stages I and II. Therefore, we propose a revised system to improve discriminative ability in stages I and II. Methods: We compared the revised J‐system with the present J‐system using Cox proportional hazards model to predict mortality rate. We also evaluated the recently proposed GAP ( G ender, A ge and P hysiology) system in comparison to both J‐systems. Results: Two‐hundred and fifteen IPF patients were studied retrospectively. A univariate model showed that the present and revised J‐systems and a modified GAP system were all significant prognostic factors. The C‐statistic for discriminating prognosis was higher in the revised J‐system than the modified GAP system and the present J‐system (0.677, 0.652 and 0.659, respectively). The C‐statistics of these models produced from the 10 000 bootstrap samples were similar to those of the original models, suggesting good internal validation (0.665 (95% CI: 0.621–0.705), 0.645 (0.600–0.686) and 0.659 (0.616–0.700), respectively). Multivariate analysis revealed that the revised J‐system ( P  = 0.0038) and the modified GAP system ( P  = 0.0029) were independent prognostic factors. Conclusion: The revised J‐system can provide a better mortality prediction than the present one. Both the revised J‐system and the modified GAP system are independent and valuable tools for prognostication and clinical management for IPF. Abstract : We propose a revised disease severity staging system for idiopathic pulmonary fibrosis (IPF) in Japan, consisting of arterial partial pressure of oxygen (PaO2 ) and exercise desaturation, and investigate its usefulness as a predictor of mortality. We show that this revised J‐system can be a valuable tool for prognostication and clinical management for IPF.